2021
DOI: 10.1097/brs.0000000000004082
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Neuromuscular Scoliosis: Results and Complications at a Minimal Follow-up of 5 Years

Abstract: Study Design. A prospective study.Objective. The aim of this study was to report the results of an alternative technique to growing rods (GR) for neuromuscular scoliosis using a minimally invasive fusionless surgery with a minimum of 5 years' follow-up. Summary of Background Data. Conservative treatment is not effective in progressive neuromuscular scoliosis. Early surgery using GR is increasingly advocated to control the deformity while preserving spinal and thoracic growth before arthrodesis. These technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
(70 reference statements)
2
18
0
Order By: Relevance
“…The BFC allowing further growth of the spine is therefore indicated in immature patients, as confirmed by our own study, allowing early removal of bracing, which has been demonstrated to have a negative impact on the quality of life and treatment satisfaction while not avoiding curve progression 36,37 . Furthermore, the solidity of the BFC makes final spinal fusion unnecessary, preventing further surgical interventions in skeletally mature patients, as demonstrated by long-term studies and recent meta-analyses 17,33,35 …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The BFC allowing further growth of the spine is therefore indicated in immature patients, as confirmed by our own study, allowing early removal of bracing, which has been demonstrated to have a negative impact on the quality of life and treatment satisfaction while not avoiding curve progression 36,37 . Furthermore, the solidity of the BFC makes final spinal fusion unnecessary, preventing further surgical interventions in skeletally mature patients, as demonstrated by long-term studies and recent meta-analyses 17,33,35 …”
Section: Discussionmentioning
confidence: 55%
“…Some less invasive constructs exist for NMS treatment to decrease complication rates while maintaining adequate curve correction 10,15,16 . Among them, a 4-rod bipolar fusionless construct (BFC), which was strongly fixed to the upper thoracic spine and to the pelvis, made it possible to avoid final fusion and presented a low rate of mechanical complications (14%) even after 5 years of follow-up 10,17 . There is, however, a current lack of studies comparing clinical and radiologic perioperative outcomes between this technique and SPF for NMS.…”
mentioning
confidence: 99%
“…MIFLS bipolar technique differs from TGR as it is definitive thanks to a solid construct relying on strong proximal and distal fixations. The stability of the results at long term and the absence of rod breakage made it possible to avoid the final arthrodesis for all patients, that was initially planned 33. This technique became the standard of surgical treatment for neuromuscular scoliosis in our department.…”
Section: Discussionmentioning
confidence: 98%
“…The stability of the results at long term and the absence of rod breakage made it possible to avoid the final arthrodesis for all patients, that was initially planned. 33 This technique became the standard of surgical treatment for neuromuscular scoliosis in our department. However, even if this construct is definitive, it remains evolutive as it allows a gradual correction of the spinal deformity thanks to further symmetric or asymmetric RL procedures if necessary, to improve the correction of residual spinal deformity or pelvic obliquity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several surgeons have been trying to apply MIS techniques for the correction of AIS, being eager to reduce surgical morbidities and bring cosmetic benefits. Moreover, efforts to reduce the surgical burden have extended to other types of deformities, such as neuromuscular scoliosis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%